Soil organic carbon, carbon sequestration, soil microbial biomass carbon and nitrogen, and soil enzymatic activity as influenced by conservation agriculture in pigeonpea (Cajanus cajan) + soybean (Gycine max) intercropping system - KUMAR, B T NAVEEN; BABALAD, H B (The Indian Journal of Agricultural Sciences, 2018)
Field experiments were conducted during the year 2014-15 and 2015-16 at MARS, Dharwad, Karnataka to study the influence of conservation agriculture (CA) practices on soil health in a pigeonpea [Cajanus cajan (L.) Millsp]+ soybean [Glycine max (L.) Merr.] intercropping system. The experiment consisted of 6 tillage systems [CT1: No tillage with broad bed and furrow (BBF) and crop residue retained on the surface, CT2: Reduced tillage with BBF and incorporation of crop residue, CT3: No tillage with flatbed and crop residue retained on the surface, CT4: reduced tillage with flatbed and incorporation of crop residue, CT5: Conventional tillage with incorporation of crop residue and CT6: Conventional tillage without crop residue]. The experiment was laid out in strip block design and replicated thrice. The CA treatments significantly improves soil health. The pooled data revealed that, all the CA systems i.e. CT1, CT2, CT3 and CT4 recorded significantly higher soil organic carbon at 0-15 cm depth (0.62, 0.64, 0.60 ad 0.62%, respectively) and 15-30 cm depth (0.56, 0.56, 0.54 and 0.55 %, respectively), higher soil carbon sequestration (15.1, 15.4, 14.6 and 14.7 t/ha, respectively) over conventional till systems. However, soil microbial biomass carbon and nitrogen were significantly higher in all the CA systems. While, significantly higher soil urease activity (11.76, 11.86, 11.10 and 11.44 Î¼g NH4-N/g/day), dehydrogenase activity (32.29, 32.29, 31.14 and 31.55 Î¼g TPF/g/day) and total phosphatase activity (173.21, 174.55, 170.09 and 173.21 Î¼g PNP/g/hr) were recorded in CT1, CT2, CT3 and CT4 over CT5 and CT6.